123456789101112131415161718192021222324252627282930313233343536373839404142434445464748495051525354555657585960616263646566676869707172737475767778798081828384858687888990919293949596979899100101102103104105106107108109110111112113114115116117118119120121122123124125126127128129130131132133134135136137138139140141142143144145146147148149150151152153154155156157158159160161162163164165166167168169170171172 |
- from sympy.core.numbers import (I, Rational)
- from sympy.core.singleton import S
- from sympy.core.symbol import (Dummy, symbols)
- from sympy.functions.elementary.exponential import log
- from sympy.functions.elementary.miscellaneous import sqrt
- from sympy.functions.elementary.trigonometric import atan
- from sympy.integrals.integrals import integrate
- from sympy.polys.polytools import Poly
- from sympy.simplify.simplify import simplify
- from sympy.integrals.rationaltools import ratint, ratint_logpart, log_to_atan
- from sympy.abc import a, b, x, t
- half = S.Half
- def test_ratint():
- assert ratint(S.Zero, x) == 0
- assert ratint(S(7), x) == 7*x
- assert ratint(x, x) == x**2/2
- assert ratint(2*x, x) == x**2
- assert ratint(-2*x, x) == -x**2
- assert ratint(8*x**7 + 2*x + 1, x) == x**8 + x**2 + x
- f = S.One
- g = x + 1
- assert ratint(f / g, x) == log(x + 1)
- assert ratint((f, g), x) == log(x + 1)
- f = x**3 - x
- g = x - 1
- assert ratint(f/g, x) == x**3/3 + x**2/2
- f = x
- g = (x - a)*(x + a)
- assert ratint(f/g, x) == log(x**2 - a**2)/2
- f = S.One
- g = x**2 + 1
- assert ratint(f/g, x, real=None) == atan(x)
- assert ratint(f/g, x, real=True) == atan(x)
- assert ratint(f/g, x, real=False) == I*log(x + I)/2 - I*log(x - I)/2
- f = S(36)
- g = x**5 - 2*x**4 - 2*x**3 + 4*x**2 + x - 2
- assert ratint(f/g, x) == \
- -4*log(x + 1) + 4*log(x - 2) + (12*x + 6)/(x**2 - 1)
- f = x**4 - 3*x**2 + 6
- g = x**6 - 5*x**4 + 5*x**2 + 4
- assert ratint(f/g, x) == \
- atan(x) + atan(x**3) + atan(x/2 - Rational(3, 2)*x**3 + S.Half*x**5)
- f = x**7 - 24*x**4 - 4*x**2 + 8*x - 8
- g = x**8 + 6*x**6 + 12*x**4 + 8*x**2
- assert ratint(f/g, x) == \
- (4 + 6*x + 8*x**2 + 3*x**3)/(4*x + 4*x**3 + x**5) + log(x)
- assert ratint((x**3*f)/(x*g), x) == \
- -(12 - 16*x + 6*x**2 - 14*x**3)/(4 + 4*x**2 + x**4) - \
- 5*sqrt(2)*atan(x*sqrt(2)/2) + S.Half*x**2 - 3*log(2 + x**2)
- f = x**5 - x**4 + 4*x**3 + x**2 - x + 5
- g = x**4 - 2*x**3 + 5*x**2 - 4*x + 4
- assert ratint(f/g, x) == \
- x + S.Half*x**2 + S.Half*log(2 - x + x**2) + (9 - 4*x)/(7*x**2 - 7*x + 14) + \
- 13*sqrt(7)*atan(Rational(-1, 7)*sqrt(7) + 2*x*sqrt(7)/7)/49
- assert ratint(1/(x**2 + x + 1), x) == \
- 2*sqrt(3)*atan(sqrt(3)/3 + 2*x*sqrt(3)/3)/3
- assert ratint(1/(x**3 + 1), x) == \
- -log(1 - x + x**2)/6 + log(1 + x)/3 + sqrt(3)*atan(-sqrt(3)
- /3 + 2*x*sqrt(3)/3)/3
- assert ratint(1/(x**2 + x + 1), x, real=False) == \
- -I*3**half*log(half + x - half*I*3**half)/3 + \
- I*3**half*log(half + x + half*I*3**half)/3
- assert ratint(1/(x**3 + 1), x, real=False) == log(1 + x)/3 + \
- (Rational(-1, 6) + I*3**half/6)*log(-half + x + I*3**half/2) + \
- (Rational(-1, 6) - I*3**half/6)*log(-half + x - I*3**half/2)
- # issue 4991
- assert ratint(1/(x*(a + b*x)**3), x) == \
- (3*a + 2*b*x)/(2*a**4 + 4*a**3*b*x + 2*a**2*b**2*x**2) + (
- log(x) - log(a/b + x))/a**3
- assert ratint(x/(1 - x**2), x) == -log(x**2 - 1)/2
- assert ratint(-x/(1 - x**2), x) == log(x**2 - 1)/2
- assert ratint((x/4 - 4/(1 - x)).diff(x), x) == x/4 + 4/(x - 1)
- ans = atan(x)
- assert ratint(1/(x**2 + 1), x, symbol=x) == ans
- assert ratint(1/(x**2 + 1), x, symbol='x') == ans
- assert ratint(1/(x**2 + 1), x, symbol=a) == ans
- # this asserts that as_dummy must return a unique symbol
- # even if the symbol is already a Dummy
- d = Dummy()
- assert ratint(1/(d**2 + 1), d, symbol=d) == atan(d)
- def test_ratint_logpart():
- assert ratint_logpart(x, x**2 - 9, x, t) == \
- [(Poly(x**2 - 9, x), Poly(-2*t + 1, t))]
- assert ratint_logpart(x**2, x**3 - 5, x, t) == \
- [(Poly(x**3 - 5, x), Poly(-3*t + 1, t))]
- def test_issue_5414():
- assert ratint(1/(x**2 + 16), x) == atan(x/4)/4
- def test_issue_5249():
- assert ratint(
- 1/(x**2 + a**2), x) == (-I*log(-I*a + x)/2 + I*log(I*a + x)/2)/a
- def test_issue_5817():
- a, b, c = symbols('a,b,c', positive=True)
- assert simplify(ratint(a/(b*c*x**2 + a**2 + b*a), x)) == \
- sqrt(a)*atan(sqrt(
- b)*sqrt(c)*x/(sqrt(a)*sqrt(a + b)))/(sqrt(b)*sqrt(c)*sqrt(a + b))
- def test_issue_5981():
- u = symbols('u')
- assert integrate(1/(u**2 + 1)) == atan(u)
- def test_issue_10488():
- a,b,c,x = symbols('a b c x', positive=True)
- assert integrate(x/(a*x+b),x) == x/a - b*log(a*x + b)/a**2
- def test_issues_8246_12050_13501_14080():
- a = symbols('a', nonzero=True)
- assert integrate(a/(x**2 + a**2), x) == atan(x/a)
- assert integrate(1/(x**2 + a**2), x) == atan(x/a)/a
- assert integrate(1/(1 + a**2*x**2), x) == atan(a*x)/a
- def test_issue_6308():
- k, a0 = symbols('k a0', real=True)
- assert integrate((x**2 + 1 - k**2)/(x**2 + 1 + a0**2), x) == \
- x - (a0**2 + k**2)*atan(x/sqrt(a0**2 + 1))/sqrt(a0**2 + 1)
- def test_issue_5907():
- a = symbols('a', nonzero=True)
- assert integrate(1/(x**2 + a**2)**2, x) == \
- x/(2*a**4 + 2*a**2*x**2) + atan(x/a)/(2*a**3)
- def test_log_to_atan():
- f, g = (Poly(x + S.Half, x, domain='QQ'), Poly(sqrt(3)/2, x, domain='EX'))
- fg_ans = 2*atan(2*sqrt(3)*x/3 + sqrt(3)/3)
- assert log_to_atan(f, g) == fg_ans
- assert log_to_atan(g, f) == -fg_ans
|